An Analysis of the Role of Islamic Education in Addressing Moral Decline in the Modern Era - Tri Rahayu Saptarini; Jasiah Jasiah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Moral decline in the modern era is reflected in the weakening of moral conduct, the increasing prevalence of deviant behaviors, the misuse of social media, and the declining level of religious awareness among students. This issue is significant because previous studies have largely positioned Islamic education as a normative subject matter rather than as a comprehensive moral development system that encompasses family, school, community, and digital environments. This study seeks to examine the role of Islamic education in addressing moral decline in the modern era and to analyze its practical contributions to the moral development of students. The study employed a literature review approach by examining Indonesian journals, scholarly articles, and books on Islamic education. The collected data were analyzed using a descriptive-critical method focusing on themes related to moral decline, moral character (akhlaq), and strategies for strengthening Islamic education. The findings reveal that Islamic education functions as a preventive safeguard against moral degradation, a medium for value internalization, a mechanism for character habituation, a source of teacher role modeling, a means of strengthening family involvement, and a framework for promoting Islamic digital literacy. The study concludes that Islamic education can effectively address moral decline when the values of faith (iman), knowledge (ilm), worship (ibadah), and moral character (akhlaq) are consistently integrated into students’ daily lives through structured, purposeful, and sustainable educational practices. Therefore, Islamic education should be implemented as a holistic and continuous process involving collaboration among educational institutions, families, communities, and digital learning environments.